Dairy production, consumption and marketing in Bangladesh - Halder, Shantana R; Barua, Proloy (BRAC Research and Evaluation Division (RED), 2020)
This study was a part of RED-Imperial College joint research, conducted in July 2003. The broad objective of this study is to review the existing milk production, consumption and marketing situation in Bangladesh and to develop policy issues on improvement of milk marketing. It is revealed that milk production in the country has been increasing but not sufficiently to meet the large demand. Like production, per capita consumption has also increased but its level across the country is still very low. Worryingly milk is another product where consumption appears to be declining for the poor as middle/upper income urban markets capture the available milk supply. The increase in collection networks both NGO and private have encouraged increased production but this has not increased consumption at the local level. In this case remoteness from markets can be an advantage nutritionally for poor producers, as they are likely to produce for home and neighbourhood consumption. Yet producers with good market access fail to fully benefit from the high urban demand, as the intermediaries capture the high margins. The most vulnerable to declining milk consumption are market dependent poor groups, the landless rural poor and slum dwellers. The urban market for processed and packaged milk products, though still very small, is expanding rapidly. Collection and distribution networks, together with chilling centres and refrigerated transport infrastructure are developing under private sector and NGO control. These provide hygienic, high quality products, whilst also providing a range of employment opportunities throughout the sector. If development could proceed so that further employment was generated whilst expanding availability to a wider range of consumers this could be a positive development.